Analysis of the role of autophagy inhibition by two complementary human cytomegalovirus BECN1/Beclin 1-binding proteins - Mouna, Lina (2015)
Autophagy is activated early after human cytomegalovirus (HCMV) infection, but lateron the virus blocks autophagy. Here we characterized 2 HCMV proteins, TRS1 andIRS1, which inhibit autophagy during infection. Expression of either TRS1 or IRS1 wasable to block autophagy in different cell lines, independently of the EIF2S1 kinase,EIF2AK2/PKR. Instead, TRS1 and IRS1 interacted with the autophagy proteinBECN1/Beclin 1. We mapped the BECN1-binding domain (BBD) of IRS1 and TRS1 andfound it to be essential for autophagy inhibition. Mutant viruses that express only IRS1or TRS1 partially controlled autophagy, whereas a double mutant virus expressingneither protein stimulated autophagy. A mutant virus that did not express IRS1 andexpressed a truncated form of TRS1 in which the BBD was deleted, failed to controlautophagy. However, this mutant virus had similar replication kinetics as wild-type virus,suggesting that autophagy inhibition is not critical for viral replication. In fact, usingpharmacological modulators of autophagy and inhibition of autophagy by shRNAknockdown, we discovered that stimulating autophagy enhanced viral replication.Conversely, inhibiting autophagy decreased HCMV infection. Thus, our resultsdemonstrate a new proviral role of autophagy for a DNA virus